2005
DOI: 10.1111/j.1365-2125.2005.02387.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical care of patients with heart failure

Abstract: AimThe aim of this study was to investigate the impact of a pharmacist-led pharmaceutical care programme, involving optimization of drug treatment and intensive education and self-monitoring of patients with heart failure (HF) within the United Arab Emirates (UAE), on a range of clinical and humanistic outcome measures. MethodsThe study was a randomized, controlled, longitudinal, prospective clinical trial at Al-Ain Hospital, Al-Ain, UAE. Patients were recruited from the general medical wards and from cardiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
190
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(192 citation statements)
references
References 41 publications
1
190
0
1
Order By: Relevance
“…Randomized controlled studies have shown that pharmacists improve medication and lifestyle adherence as part of a multidisciplinary team. [36][37][38][39][40] Some of these studies also demonstrated improvements in patients' clinical outcomes. 36,37,[39][40][41] Studies Assessing Medication Adherence A summary of studies evaluating pharmacist interventions on medication adherence is presented in Table 3.…”
Section: Pharmacist Interventions To Improve Adherencementioning
confidence: 99%
See 3 more Smart Citations
“…Randomized controlled studies have shown that pharmacists improve medication and lifestyle adherence as part of a multidisciplinary team. [36][37][38][39][40] Some of these studies also demonstrated improvements in patients' clinical outcomes. 36,37,[39][40][41] Studies Assessing Medication Adherence A summary of studies evaluating pharmacist interventions on medication adherence is presented in Table 3.…”
Section: Pharmacist Interventions To Improve Adherencementioning
confidence: 99%
“…Though not powered to detect, the composite endpoint of all-cause mortality, hospital admissions, and ED visits was not significantly different between the 2 groups (intervention 60%, control 67%, HR = 0.85, 95% CI = 0.55-1.40). Sadik et al (2005) assessed structured pharmaceutical care versus traditional care in 208 HF patients in the United Arab Emirates. 36 The intervention integrated a treatment algorithm, patient education, and self-monitoring through diary cards.…”
Section: Pharmacist Interventions To Improve Adherencementioning
confidence: 99%
See 2 more Smart Citations
“…This has manifested as improved control of chronic diseases, improvements in adherence, reduced medication spend per patient, and diminished hospital costs. [42][43][44] These findings have led to renewed calls for in-person pharmacist counseling and follow-up to improve medication taking behavior. 45 Related to these study findings, the next steps may involve: 1) Pharmacist follow-up to ensure patients are contacted when they have a medication on record that they have not picked up, coupled with patient education of the importance of taking it as directed.…”
Section: Discussionmentioning
confidence: 99%